The effect of magnesium on the inflammatory response in human vascular endothelial cells - Almousa, Lujain (2018)
Magnesium plays several physiological roles, including the formation of bones and teeth, muscle contraction, and cardiovascular function. Magnesium deficiency affects cardiovascular health through the modulation of endothelial cell function, particularly by having a negative impact on endothelial cell proliferation, increasing monocyte adhesion, inhibiting cell migration and markedly altering endothelial cell gene expression. With the recognition of the protective role of magnesium in endothelial cells, the aim of this study was to investigate the effects of magnesium sulphate on human umbilical vein endothelial cells (HUVECs) proliferation, gene expression, and the pro-inflammatory response caused by a bacterial endotoxin lipopolysaccharide (LPS). After culture for 120 hours in low (0.1mM) and high (5mM) magnesium, the viability of HUVECs decreased in the low magnesium (P=0.024), whilst the proliferation of HUVECs increased in the high magnesium (P=0.016). Moreover, exposing the cells to LPS lowered viability in the culture with low magnesium (P=0.002), but high magnesium protected the HUVECs from LPS-induced cell death (P=0.037). Magnesium dose-dependent gene expression profiles of HUVECs were investigated via microarray, revealing extensive effects of low and high magnesium on the transcriptome (2930 up-regulated genes and 2828 down-regulated genes). Magnesium deficiency in endothelial cells activated inflammatory pathways through the transcription factor nuclear factor κB (NF-κB), which plays an important role in the early pathology of atherosclerosis. LPS-treated HUVECs cultured in low magnesium showed up-regulation of mRNA expression for pro-inflammatory factors, such as ICAM-1, VCAM-1, IL-8, and MCP-1, and the expression of cytokine proteins, including IL-2, IL-3, IL-8, IL-15, MCP-1, GRO, and GROa. In contrast, high magnesium decreased the expression of IL-6 and MCP-1 mRNA and the protein concentrations of IL-2 and IL-6. The study found that LPS activates the NF-κB pathway through the TLR2 and TLR4 receptors and this pathway was inhibited by high magnesium concentration. Overall, the work presented demonstrates that inflammatory processes in vascular endothelial cells are sensitive to magnesium. This suggests that magnesium nutrition may be an overlooked factor in CVD and is worthy of further investigation.